A photovoice study on pre-service EFL teachers’ struggles for managing students’ misbehavior during teaching practicum - Lisa Amalia Solicha (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
Despite classroom management has been widely investigated by previous studies, the issues of managing students’ misbehavior in EFL classes still receive scanty attention. This study aims to investigate the types of students’ misbehavior and pre-service EFL teachers’ struggles in managing students’ misbehavior during their teaching practicum in secondary schools. This research was designed as a photovoice study, and two pre-service EFL teachers were recruited to participate in this study. Their lived experiences in dealing with students’ misbehavior during a teaching practicum program were documented through photovoice. The data were analyzed employing thematic analysis. The study findings demonstrated three types of students’ misbehavior, i.e. socially disruptive behavior, authority-challenging behavior, and self-disruptive behavior. Another finding reported that pre-service teachers encountered several challenges in managing students’ misbehavior, in terms of managing hard-control students, maintaining students’ focus, managing students who made noise, and organizing students who broke classroom rules. This research concludes with empirical insights into how pre-service teachers encounter challenges addressing students’ misbehavior and how they require to use strategies to tackle students’ misbehavior, including giving punishments regarding the level of students’ misbehavior.